The Influence of Brand Equity, Mobile Banking Usage on Customer Loyalty Mediated by Customer Satisfaction - Jelita Lanmora Lubis; Usep Suhud; Agung Wahyu Handaru (MultiTech Publisher, 2025)
This study aims to explore the effect of brand equity and mobile banking usage on customer loyalty of Islamic Banks, with customer satisfaction as a mediating variable. This study used a quantitative approach with survey method. Data was collected from 250 respondents who are active customers of Bank Syariah. Data analysis was conducted using Structural Equation Modeling (SEM) AMOS. The findings show that brand equity has a positive and significant influence on customer loyalty and customer satisfaction. In addition, the use of mobile banking also contributes significantly to increasing customer loyalty and satisfaction. Customer satisfaction is proven to act as a mediator that strengthens the relationship between brand equity and customer loyalty.